Intraoperative Infusion-related Jet Stream Enlargement of Macular Hole. Issue 5 (May 2016) - Zacharias, Leandro C.; Rezende, Flávio A.; Suzuki, Ana Claudia F.; Tanaka, Tatiana; Azevedo, Breno Marques da Silva; Takahashi, Walter Y.
Abstract : Supplemental Digital Content is Available in the Text.